La conquête du littoral « indien » d’Afrique du Sud - Sylvain Guyot; Julien Dellier (EchoGéo)
The “Indian” south African coastline can be understood as a frontier. Its conquest is strategic for different groups (English-speaking, Afrikaners, Zulus, Xhosas etc.) and implies specific economic valorisations (seaports, industries, tourism, nature conservation, agriculture) grounded in time (pre-colonial, colonial, apartheid and post-apartheid) and space (different modes of territorial appropriation). Opposed types of coastal valorisation and various stakeholders open the way to hard conflicts. Different phases of this seafront conquest, with particular reference to the current post-apartheid connection to globalisation dynamics, are enlightened by examples linking history, stakeholders and various coastal development options. The “neo-colonisation process” of this southern frontier of the African continent by outside forces implies problematic stakes like poor integration of local people, privatisation of the coastal zone and contradictory environmental management.